Karl Marx historical dialectics, cultural education and Nigeria’s economic goals (2019)
Education is an important tool in achieving sustainable peace. Where there is no peace, chaos, destruction of lives and properties are inevitable, there will not be development therefore, stagnation and retrogression will be the likely outcomes. Knowledge is very essential to ensure peace and stability in any society. This can be achieved through the process of education. For a state or society to achieve sustainable peace, the quality and practice of its education becomes very essential. This paper examined the concepts of education and peace. It provides a philosophical insight into the various ways the process of education in Nigeria can be employed to achieve sustainable peace. The study reveals that curriculum, pedagogy and subject approaches are vital in inculcating social values and peace in the society. They are required if the potency and efforts of the process of education in strengthening and promoting peace will not be defeated. It concluded by stating that while proven and effective programmes and curriculum are in place in Nigeria's educational policy, educators have what it takes to demonstrate, impart and help learners to develop and reflect the culture of peace through classroom interactions. It finally suggested ways of promoting peace through education. This include creation of conducive atmosphere for learning, allocation of adequate funds for educational development, discouraging quota System, separating religion from secular education and provision of culturally relevant curriculum